2017
DOI: 10.1190/geo2016-0483.1
|View full text |Cite
|
Sign up to set email alerts
|

Detecting gas leakage using high-frequency signals generated by air-gun arrays

Abstract: Recent field experiments have demonstrated that marine air gun arrays create acoustic energy above 1 kHz. In this work, we suggest to use the high-frequency signal as a source to look for gas leakage at for instance a producing hydrocarbon field, or a CO2 storage site where the field is covered by permanent acoustic sensors at the seabed, often referred to as a PRM (Permanent Reservoir Monitoring) field. The only needed modification is that the temporal sampling interval for the receivers is decreased to 0.1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, measurements with broadband hydrophones have revealed that the acoustic signal from air-gun arrays contains frequencies up to tens of kHz (Goold and Fish, 1998;Tashmukhambetov et al, 2008;Landrø et al, 2011;Guan et al, 2015). Such high frequencies are much weaker than the low-frequency parts and do not benefit seismic imaging, but they can be used, for example, to detect targets of size between 0.5 and 20 m in the water column (Banda and Blondel, 2016) or for detection of potential gas leakage from an oil and gas production field or a CO 2 storage site (Landrø et al, 2017). These high frequencies might impact cetacean species that are sensitive to acoustic signals in the high-frequency range (10-150 kHz) (Ketten, 2004;Landrø et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, measurements with broadband hydrophones have revealed that the acoustic signal from air-gun arrays contains frequencies up to tens of kHz (Goold and Fish, 1998;Tashmukhambetov et al, 2008;Landrø et al, 2011;Guan et al, 2015). Such high frequencies are much weaker than the low-frequency parts and do not benefit seismic imaging, but they can be used, for example, to detect targets of size between 0.5 and 20 m in the water column (Banda and Blondel, 2016) or for detection of potential gas leakage from an oil and gas production field or a CO 2 storage site (Landrø et al, 2017). These high frequencies might impact cetacean species that are sensitive to acoustic signals in the high-frequency range (10-150 kHz) (Ketten, 2004;Landrø et al, 2011).…”
Section: Introductionmentioning
confidence: 99%